EDUKASI MENGENAI INFORMASI BOHONG (HOAKS) DI KALANGAN GURU BERBASIS LITERASI - Brillianing Pratiwi; Mohammad Adning (Universitas Terbuka, 2022)
The purpose of this study was to analyze the educational needs of teachers regarding hoaxes and provide preventive measures to prevent hoaxes among teachers. This study uses a qualitative method with a case study approach. The results of this study indicate the importance of education programs regarding hoax information among teachers so that teachers do not immediately conclude the contents of the news without reading in detail about the contents of the news. In addition, teachers have more literacy awareness in seeking clarification of the truth about a hoax, reducing the rapid spread of hoaxes, and being able to spread digital literacy skills to students. Teachers as professionals have a strategic role to realize the vision of learning implementation. The development of science and technology brings logical consequences to the orientation of the development of teacher professionalism. The conclusion of this study is that a teacher needs to have digital literacy skills so that they are able to disseminate correct information.